A Semiotic Study On Born This Way Lyric By Lady Gaga - Pribadi, Nonanda (Universitas Muhammadiyah Sumatera Utara, 2021)
This research deals with the study of semiotics analysis on the song lyrics of Bron This Way by Lady Gaga. This study mainly aims to investigate several things as follows: first, to investigate the denotative meaning, connotative meaning and myth meaning contained in the song lyrics, second was to investigate how the realization of the semiotic meaning in the lyrics of the song Born This Way. The research was applied descriptive qualitative method. The research data was in the form of the written text or transcript of the song lyrics. There are 16 signs collected that were analyzed through the application of Miles and Huberman's theory where data reduction, data presentation, and conclusion drawing or verification were carried out significantly. The results of the data analysis shown that the song lyrics have denotation, connotation meaning, and myth meaning. After getting the semiotic term in the lyrics of the song Born This Way, which at first conveyed a very familiar motivational message because in it there was a defense of minority groups who were victims of discrimination. In general, the meaning of the lyrics of the song Born This Way contains a human being who must accept the situation as it is and love himself even though the person deviates from the prevailing norms in society without changing himself to be better. There were 3 semiotic terms which were manifested in the lyrics of the song Born This Way, namely: divinity, sincerity, simplicity.